Eye-Tracking Metrics for Figure-Copying Processes in Early- vs. Late-Onset Alzheimer's Disease - Kim, Ko Woon; Choi, Jongdoo; Chin, Juhee; Lee, Byung Hwa; Na, Duk L. (Frontiers in Neurology, 2022)
Visuospatial dysfunction is a common symptom in patients with Alzheimer's disease (AD). To more focus on copying processes rather than on finally completed figures, we conceptually split the copying processes into three stages: visuoperceptual function, visuoconstructional function, and working memory function. We constructed perceptual and working spaces to investigate the different stages of copying, and then, we compared the number and duration of fixations and saccades and the number of switches across the two spaces. We used eye-tracking glasses to assess eye-tracking metrics in patients with early-onset AD (EOAD), patients with late-onset AD (LOAD), and normal control (NC) participants while they copied the simplified Rey–Osterrieth complex figure test (RCFT). Regarding eye metrics on the perceptual space, the number and duration of fixations were greater in both groups of patients with AD than in the NC participants group (number: EOAD vs. NC: p < 0.001, LOAD vs. NC: p = 0. 003/ duration: EOAD vs. NC: p < 0.001, LOAD vs. NC: p < 0.001). On the working space, the number and duration of fixations were greater in the patients with EOAD than in the patients with LOAD and NC participants (number: EOAD vs. LOAD: p = 0. 007, EOAD vs. NC: p = 0. 001/duration: EOAD vs. LOAD: p = 0. 008, EOAD vs. NC: p = 0. 002). The number of saccades and switching was higher in patients with EOAD than in NC participants (p < 0.001). The eye-tracking metrics from the simplified RCFT correlated with the neuropsychological test scores. Patients with EOAD and LOAD achieved the same level of performance at the simplified and original RCFT scores. However, patients with EOAD than LOAD showed a greater number and duration of fixations on the working space and more frequent switching between the perceptual and working spaces, which may reflect more cognitive efforts to achieve the same level of performance.